Advances in Research at Synthesis Process Optimization and Quality Standard Improvement of O-desmethylvenlafaxine Succinate - Yang, Shiwei; Chen, Shiyun; Wang, Cheng; Zhang, Shibo; Li, Shuaifei; Yuan, Xinsong; Peng, Fuyun; He, Yong (Frontiers in Chemistry, 2022)
We herein describe an optimal approach for the efficient synthesis of O-desmethylvenlafaxine succinate monohydrate (DVS) with high yield and high purity through 5-step reactions, including benzyl protection of the phenolic hydroxyl group, cyclohexanone condensation, deprotection, cyano reduction, dimethylation, and succinic acid salt formation from p-hydroxybenzene acetonitrile as a starting material. 4-Benzyloxyphenylacetonitrile (intermediate I) was prepared by the hydroxyl protection of the bromide benzyl-p-hydroxyphenylacetonitrile catalyzed by potassium carbonate with 99.83% purity and 98.92% yield. The 1, 2-nucleophilic addition of intermediate I to cyclohexanone promoted by sodium hydroxide with the homogeneous catalyst (n-Bu)4N+Br- to the preparation of 1-[Cyano(4-benzyloxyphenyl)methyl]cyclohexanol (Intermediate II) was obtained by 99.13% purity and 99.71% yield. Cyclohexanone residues and benzyl bromide residues were trace, and tetrabutylammonium bromide residues are UNDER 0.7ppm, which further improves the residual standards for genotoxic impurities (GIs). 1-[2-amino-1-(4-hydroxyphenyl)ethyl]cyclohexanol hydrochloride (Intermediate III) was prepared by 10% palladium-carbon under 2.0 MPa up to 98.32% purity and 94.20% yield. O-desmethylvenlafaxine (ODV) was synthesized by dimethylation of intermediate III with 37% formaldehyde solution and 85% formic acid solution. The highest purity was up to 99.20% and the yield was up to 84.77%. O-desmethylvenlafaxine succinate monohydrate (DVS) was formed from succinic acid and O-desmethylvenlafaxine (ODV) and crystallized in a mixed solvent of acetone and water (3:1) to obtain 99.92% purity and 90.27% yield. The 5-step total yields of desvenlafaxine succinate monohydrate is 71.09%, and its crystal form has characteristic peaks at 5 min, 10 min, 21 min, and 26 min by XRD powder diffraction, wich is consistent to the crystalline form I. Compared with conventional synthesis strategy, we revealed a novel and green process with a high total yield, high atomic economy, low environmental pollution, high operational safety, and high residual standards for genotoxic impurities (GIs), which improves drug safety.